Tatalaksana Non-Farmakologis pada Dysmenorrhea Primer: Literature Review - Ananda, Amallia; Ratna Dewi Puspita Sari; Septia Eva Lusina; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2025)
Dysmenorrhea is pain or cramps felt in the lower abdomen before or during menstruation. Dysmenorrhea is one of the most common problems experienced by adolescents and adult women. Dysmenorrhea is often accompanied by other symptoms such as dizziness, fatigue, sweating, back pain, headache, nausea, vomiting, and diarrhea. There are 2 types of dysmenorrhea, namely primary dysmenorrhea and secondary dysmenorrhea. Dysmenorrhea has a negative impact on women's quality of life. Pharmacological management has side effects of treatment, so there is a need for safer and more effective non-pharmacological management to reduce the intensity of dysmenorrhea pain. Non-pharmacological therapy consists of various non-invasive or minimally invasive treatments. This study uses a literature observation method or literature review, where the main sources of scientific articles come from national and international journals. The articles used in this study were articles published within a period of 5 years, namely 2020-2025 through the electronic databases PubMed and Google Scholar which were selected based on exclusion criteria and inclusion criteria. The purpose of this literature review is to determine non-pharmacological management of dysmenorrhea. The results of the literature review found 21 articles showing that there are several non-pharmacological therapies that are safe and effective in reducing the intensity of pain felt by dysmenorrhea sufferers such as Transcutaneous electrical Nerve Stimulation (TENS), music therapy, acupuncture, acupressure, warm compresses, exercise or aerobic exercise, and aromatherapy.